Volunteering during the COVID-19 Pandemic: An Investigation of the Motivations, Benefits, Challenges, and Concerns Associated with Volunteering during a Global Health Crisis - Erin Shimizu; Sinéad M. Hynes (European Journal of Volunteering and Community-Based Projects)
Since the beginning of the COVID-19 pandemic, there has been limited research on why people choose to volunteer or what the benefits and challenges of volunteering are, has been conducted in the context of the COVID-19 pandemic. This study aimed to investigate the motivations, benefits, challenges, and concerns associated with volunteering during the COVID-19 pandemic in Ireland. A cross-sectional design assessed the motivations, benefits, challenges, and concerns associated with volunteering during the COVID-19 pandemic. Purposive sampling was used, gathering 254 valid participants. Descriptive statistics, inferential statistics and content analysis were employed to analyse the data. Altruistic motivations, social benefits, and concerns about COVID-19 infection were among the most highly rated motivations, benefits, and concerns. Positive and negative aspects of volunteering during the COVID-19 pandemic were also identified. This study is the first of its kind to explore motivations, benefits, and challenges associated with volunteering during the COVID-19 pandemic in Ireland.